2008
DOI: 10.1590/s0074-02762008000700007
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Plasmodium spp. infection in Tierralta, Colombia

Abstract: With the aim of determining the prevalence of asymptomatic Plasmodium spp. infection by thick smear and PCR and its association with demographic and epidemiological characteristics in the village of Nuevo Tay, Tierralta, Córdoba, Colombia, a cross-sectional population study was carried out, using random probabilistic sampling. Venous blood samples were taken from 212 people on day 0 for thick smear and PCR. Clinical follow-up and thick smears were carried out on days 14 and 28. The prevalence of Plasmodium spp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 24 publications
4
42
1
2
Order By: Relevance
“…In Brazil, 16 submicroscopic PCR-positive persons with asymptomatic Plasmodium vivax infection were followed for 30 days; three-quarters were PCR-negative at 2 weeks, while the remaining four remained PCR-positive at 30 days, with none developing symptoms [26]. In serial cross-sectional studies conducted in Colombia and Peru, roughly half of smear-positive asymptomatic infections spontaneously cleared within 14 days in Colombia (13/24) and within 7 days in Peru (16/30) [27,28,29]. As for the rest, the majority remained asymptomatic at follow-up, with half of those in the Peru study showing decreased parasitemia at day 7, and 25% of those in the Colombian study remaining parasitemic at day 14.…”
Section: The Asymptomatic Reservoir Is Heterogeneous In Terms Of Persmentioning
confidence: 99%
“…In Brazil, 16 submicroscopic PCR-positive persons with asymptomatic Plasmodium vivax infection were followed for 30 days; three-quarters were PCR-negative at 2 weeks, while the remaining four remained PCR-positive at 30 days, with none developing symptoms [26]. In serial cross-sectional studies conducted in Colombia and Peru, roughly half of smear-positive asymptomatic infections spontaneously cleared within 14 days in Colombia (13/24) and within 7 days in Peru (16/30) [27,28,29]. As for the rest, the majority remained asymptomatic at follow-up, with half of those in the Peru study showing decreased parasitemia at day 7, and 25% of those in the Colombian study remaining parasitemic at day 14.…”
Section: The Asymptomatic Reservoir Is Heterogeneous In Terms Of Persmentioning
confidence: 99%
“…Several epidemiological studies have shown that cases of asymptomatic malaria are highly prevalent in many endemic regions (Cucunubá et al 2008, Baliraine et al 2009, Marangi et al 2009, Steenkeste et al 2010. Individuals with asymptomatic Plasmodium infection can exhibit low parasitaemia for up to 60 days (Alves et al 2002).…”
mentioning
confidence: 99%
“…The prevalence of sub-patent parasitaemias ranged from 0–33% regardless of age, based on thick smear assays in areas of high malaria transmission on the Pacific coast (Terrientes et al 1994, González et al 1997, Mendez et al 2000, Osorio et al 2004). In the northern area of Colombia (Tierralta, Cordoba), the prevalence of Plasmodium infection was approximately 18%, whereas the prevalence of asymptomatic infection as measured with polymerase chain reaction was 15% (Cucunubá et al 2008). Although there is a lack of systematic studies in LA to determine the grade of clinical immunity and its correlation with age, the high prevalence of subclinical infection observed in LA suggests that individuals who are permanently exposed to malaria acquire a level of immunity that allows them to live a normal life.…”
Section: Acquired Immunity and Evidence Of Malaria Immune Protection mentioning
confidence: 99%